Praktik Ritual Mopo’a Huta (Memberi Makan pada Tanah) pada Masyarakat Gorontalo di Desa Molamahu - Momy A. Hunowu; Hatim Badu Pakuna (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2020)
The mopo’a huta ritual is a ritual practiced by Gorontalo people when the dry season arrives. By carrying out this ritual, people believe that rain will fall and fertility and prosperity will come. This ritual has been carried out since hundreds of years ago, but nowadays it has begun to be opposed by several groups. This study aims to find out how the practice of the mopo'a Huta ritual, how the public view of the mopo'a huta ritual using Geertz's perspective. The study used a qualitative approach with case studies, conducted interviews with the organizers, made observations during the procession, and explored the results of previous research. The study found that the mopo'a huta ritual in practice held a dance (dayango) accompanied by the wasps of towohu (drums) for several nights. At the peak of the ritual, offerings were made consisting of certain ingredients to be presented to supernatural beings as the rulers of nature. For this practice, there are 3 community groups 1) the abangan group, namely the traditional farmers who still hold the tradition, 2) the santri group, namely the educated community as a group of modern farmers, some of whom still believe and some do not believe because there is already technology that can solve problems, 3) priyai groups, namely village heads. In the past, the village head was the main supporter of the mopo'a huta ritual, while at present, the village head secures himself in the middle position.